2001
DOI: 10.1073/pnas.231243698
|View full text |Cite
|
Sign up to set email alerts
|

Vanilloid receptor expression suggests a sensory role for urinary bladder epithelial cells

Abstract: P ainful sensations induced by capsaicin, the pungent substance in hot peppers, are caused by stimulation of vanilloid receptor 1 (VR1), an ion channel protein expressed by nociceptive primary afferent neurons. VR1 also participates in the detection of at least two additional noxious stimuli, acid (pH Ͻ 6) and heat (Ͼ43°C). The urinary bladder is rich with capsaicinsensitive afferent fibers that detect bladder distension or the presence of irritant chemicals and in turn trigger reflex bladder activity. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
389
1
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 473 publications
(419 citation statements)
references
References 26 publications
20
389
1
4
Order By: Relevance
“…A similar mechanism exists in the mouse urinary bladder, where urinary epithelial cell TRPV1 is required for hypoosmolarity-evoked release of ATP (37), which in turn appears to be detected by P2X3 (ATP-gated ion channel subtype three)-containing nerve terminals in the bladder wall (42). Alternative candidate heat-evoked signaling molecules include nitric oxide, which also undergoes TRPV1-dependent release from urinary epithelial cells (43), as well as prostaglandins and platelet-activating factor, which have been shown to be released from keratinocytes in response to UV radiation (44), extreme heating, oxidative stress (25), or, in human keratinocytes, capsaicin-evoked activation of TRPV1 (21). Biochemical analysis of supernatants from warmth-treated keratinocytes would allow the "soluble messenger" hypothesis to be tested experimentally, as would the analysis of thermosensation and thermoregulation in mice lacking TRPV4 selectively in keratinocytes.…”
Section: Discussionmentioning
confidence: 89%
“…A similar mechanism exists in the mouse urinary bladder, where urinary epithelial cell TRPV1 is required for hypoosmolarity-evoked release of ATP (37), which in turn appears to be detected by P2X3 (ATP-gated ion channel subtype three)-containing nerve terminals in the bladder wall (42). Alternative candidate heat-evoked signaling molecules include nitric oxide, which also undergoes TRPV1-dependent release from urinary epithelial cells (43), as well as prostaglandins and platelet-activating factor, which have been shown to be released from keratinocytes in response to UV radiation (44), extreme heating, oxidative stress (25), or, in human keratinocytes, capsaicin-evoked activation of TRPV1 (21). Biochemical analysis of supernatants from warmth-treated keratinocytes would allow the "soluble messenger" hypothesis to be tested experimentally, as would the analysis of thermosensation and thermoregulation in mice lacking TRPV4 selectively in keratinocytes.…”
Section: Discussionmentioning
confidence: 89%
“…It remains to be determined whether this down-regulation is part of a compensatory mechanism or a consequence of LPS-induced death and shedding of urothelial cells. 17 As the urothelium works with underlying afferent nerves to detect the presence of irritant stimuli, 25 it will be of value to determine whether CD14, integrin ␣ 7, and MMP11 are part of the unique set of urothelial genes contrasting with those found in the bladder detrusor muscle. Ongoing experiments in this laboratory are determining which genes are uniquely expressed by each of the urinary bladder layers.…”
Section: Gene Up-regulation By Chronic Lps Stimulationmentioning
confidence: 99%
“…Recent research, however, has indicated that VR1 is also distributed in some non-nervous tissues, such as liver, lungs, gastric epithelial cells [17] , bronchi [18] , bladder epithelium [19] , mast cells, skin cells [20] , and macrophages [21] . This finding suggests that VR1 might be involved in regulating a variety of physiological functions of different tissues and organs.…”
Section: Discussionmentioning
confidence: 99%